Dendritic morphology of motor neurons and interneurons within the compact, semicompact, and loose formations of the rat nucleus ambiguus - Fogarty, Matthew J. (Frontiers in Cellular Neuroscience, 2024)
Introduction Motor neurons (MNs) within the nucleus ambiguus innervate the skeletal muscles of the larynx, pharynx, and oesophagus. These muscles are activated during vocalisation and swallowing and must be coordinated with several respiratory and other behaviours. Despite many studies evaluating the projections and orientation of MNs within the nucleus ambiguus, there is no quantitative information regarding the dendritic arbours of MNs residing in the compact, and semicompact/loose formations of the nucleus ambiguus.. Methods In female and male Fischer 344 rats, we evaluated MN number using Nissl staining, and MN and non-MN dendritic morphology using Golgi–Cox impregnation Brightfield imaging of transverse Nissl sections (15 μm) were taken to stereologically assess the number of nucleus ambiguus MNs within the compact and semicompact/loose formations. Pseudo-confocal imaging of Golgi-impregnated neurons within the nucleus ambiguus (sectioned transversely at 180 μm) was traced in 3D to determine dendritic arbourisation. Results We found a greater abundance of MNs within the compact than the semicompact/loose formations. Dendritic lengths, complexity, and convex hull surface areas were greatest in MNs of the semicompact/loose formation, with compact formation MNs being smaller. MNs from both regions were larger than non-MNs reconstructed within the nucleus ambiguus. Conclusion Adding HBLS to the diet could be a potentially effective strategy to improve horses’ health.